PERAN KUALITAS JASA PADA KEPUASAN SERTA DAMPAKNYA TERHADAP LOYALITAS DAN NIAT BERALIH NASABAH PT PEGADAIAN DI SURABAYA - Addis Al Hazmi; Emma Yulianti (Journal of Business & Banking, 2013)
This research examines the effect of service quality on satisfaction and its impact on customer loyalty and intention to switch of the customers of PT. Pegadaian in Surabaya. There were four important variables: service quality, customer satisfaction, customer loyalty and intention to switch were discussed for better understanding of consumer behavior. The research employs a structural equation modeling method based on the data collected from105 customers of PT Pegadaian in Surabaya. This research uses purposive sampling technique to determine the sample size. The result shows that Service Quality has significant and positive influence towards customer Satisfaction. In addition, Customer Satisfaction has influence towards Customer Loyalty and Customer Intention to Switch.